Efficient storage, retrieval and analysis of poker hands: An adaptive data framework - Gorawski, Marcin; Lorek, Michał (Zielona Góra: Uniwersytet Zielonogórski)
In online gambling, poker hands are one of the most popular and fundamental units of the game state and can be considered objects comprising all the events that pertain to the single hand played. In a situation where tens of millions of poker hands are produced daily and need to be stored and analysed quickly, the use of relational databases no longer provides high scalability and performance stability.
Keywords: big data; storage model design; data architecture; data access path optimization